Typology of vaccine refusals on Facebook in Malaysia - Wan Mohd Ghazali, Wan Norshira; Idris, Hamidah; Mohamed, Shafizan; Mohd Nasir, Nur Shakira (Taylor’s University, 2021)
Vaccine success stories in eradicating infectious diseases such as smallpox and polio have long been acknowledged. However, the function of vaccines is not widely known currently as these diseases are low profile. Studies have shown that social media users have always disseminated the harmful effects of vaccines on health without referring to valid and credible sources. This has led to an increase in anti-vaccine sentiment among the public and contributed to vaccine refusal around the globe, including Malaysia. Facebook is well known for providing the space for anti-vaxxers to engage and share distorted and unfounded views about vaccination. Therefore, this study is conducted to examine anti-vaxxers on Facebook and to understand their characteristics. A total of 456 Facebook users who claimed to reject vaccines publicly on a selected Facebook page, Malaysia Kene Tahu (MKT), were quantitatively profiled. The results show that the majority used genuine profile accounts while revealing only certain demographic information. There are three main categories of anti-vaxxers on Facebook based on their anti-vaccination content sharing, namely persistent, moderate, and uncertain. Although only a few people were persistent in sharing vaccine misinformation, this study argues that the impact could be detrimental as their personal Facebook is publicly visible which might influence other users. In conclusion, more strategic communication interventions involving various different stakeholders is needed to educate Facebook users against vaccine misinformation.